KEHADIRAN KAUM WANITA MUSLIMAH DALAM SHALAT JUM’AT (Studi Kasus Beberapa Masjid di Belanda) - Shofwatul Aini (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2015)
Muslim women are not obliged to attend the congregational prayers, especially Friday prayers (ŝalāt al-Jumu’ah). However, it is merit notice that some Muslim women in the Netherlands attend the Friday prayers voluntarily. This article tries to elucidate why they do so; what factors motivate them. In relation to this matter, some other questions, such as the attendance of women in mosques, the arrangement of men and women in mosques, and sermons, will also be studied. This study unravels the questions from two dimensions, normative and empirical. Especially relating to sermons, the study will be focused on three elements: the persons giving the sermons, the materials of the sermons, and the audience of the sermons.